Induced pluripotent stem cell-derived enteric neural crest cells repopulate human aganglionic tissue-engineered intestine to form key components of the enteric nervous system. (April 2020) - Chang, David F; Zuber, Samuel M; Gilliam, Elizabeth A; Nucho, Laura-Marie A; Levin, Gabriel; Wang, Fengnan; Squillaro, Anthony I; Huang, Sha; Spence, Jason R; Grikscheit, Tracy C
Models for enteric neuropathies, in which intestinal nerves are absent or injured, are required to evaluate possible cell therapies. However, existing options, including transgenic mice, are variable and fragile. Here immunocompromised mice were implanted with human pluripotent stem cell–derived tissue-engineered small intestine 10 weeks prior to a second survival surgery in which enteric nervous system precursor cells, or saline controls, were injected into the human intestinal organoid–derived tissue-engineered small intestine and analyzed 4 weeks later. Human intestinal organoid–derived tissue-engineered small intestine implants injected with saline as controls illustrated formation of intestinal epithelium and mesenchyme without an enteric nervous system. Second surgical introduction of human pluripotent stem cell–generated enteric nervous system precursors into developing human intestinal organoid–derived tissue-engineered small intestine implants resulted in proliferative migratory neuronal and glial cells, including multiple neuronal subtypes, and demonstrated function in contractility assays.